Analisis Motivasi Ekstrinsik di PT. Digivla Indonesia - Olivia Toguiboto Rambe; Christian Wiradendi Wolor; Marsofiyati, Marsofiyati (Pusat Riset dan Inovasi Nasional, 2023)
This research was conducted using qualitative descriptive methodology that requires identifying and analyzing the problems found. Qualitative research is based on primary data and secondary data. Primary data are obtained by conducting observations, interviews, and documentation, while secondary data are obtained through books, previous research, and articles directly related to research. The purpose of this study was to determine extrinsic motivation in PT. Digivla Indonesia by analyzing obstacles and solutions to overcome extrinsic motivation in employees and companies. From the results of this study, it can be seen that PT. Digivla Indonesia has provided concrete examples of the implementation of extrinsic motivation regularly and periodically, but not all employees get equal attention. This can be seen from the employee's answer regarding the level of extrinsic motivation provided is very lacking, and some divisions have not been able to carry out tasks in accordance with deadlines, so regular supervision is needed for companies to provide extrinsic motivation.